1995
DOI: 10.1287/mnsc.41.1.129
|View full text |Cite
|
Sign up to set email alerts
|

The Demand for Parimutuel Horse Race Wagering and Attendance

Abstract: There has been a long history of patron participation in parimutuel horse race wagering and attendance, which are major recreational products in consumer budgets. In this paper, the demand for parimutuel horse race wagering and attendance has been specified and estimated for both Thoroughbred and Standardbred racetracks in a multistate market area. The data are annual over the period 1960--1987. It is found that demand is price elastic in every case. Racing quality, personal income, the number of racing days, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 15 publications
2
18
0
Order By: Relevance
“…The available evidence seems to support this suggestion, as most studies have found that lotteries cannibalize pari-mutuel and racing wagers both by a patronage effect and by a spending effect (Gulley & Scott, 1989;Miers, 1996;Mobilla, 1992;Simmons & Sharp, 1987;Thalheimer & Ali, 1995a, 1995bVasche, 1990). Studies have reported losses in pari-mutuel GGR of around 10-20% following the introduction of lotteries (Gulley & Scott, 1989;Simmons & Sharp, 1987;Vasche, 1990), but despite this substitution, net state revenue is positive (Vasche, 1990).…”
Section: Lotteriesmentioning
confidence: 97%
“…The available evidence seems to support this suggestion, as most studies have found that lotteries cannibalize pari-mutuel and racing wagers both by a patronage effect and by a spending effect (Gulley & Scott, 1989;Miers, 1996;Mobilla, 1992;Simmons & Sharp, 1987;Thalheimer & Ali, 1995a, 1995bVasche, 1990). Studies have reported losses in pari-mutuel GGR of around 10-20% following the introduction of lotteries (Gulley & Scott, 1989;Simmons & Sharp, 1987;Vasche, 1990), but despite this substitution, net state revenue is positive (Vasche, 1990).…”
Section: Lotteriesmentioning
confidence: 97%
“…They find the number of slots to have a significantly negative effect on lottery sales, but horse and dog racing have no effect. Thalheimer and Ali (1995) model attendance and handle at three horse racetracks in the Ohio-Kentucky border market from 1960 to 1987. They find that the lottery (measured by payout rate) reduces the handle at racetracks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some of the papers that address interindustry relationships are of Elliot and Navin (2002), Fink and Rork (2003), Grote and Matheson (2006), Gulley and Scott (1989), Kearney (2005), Mobilia (1992), Ray (2001), Siegel and Anders (2001), Thalheimer and Ali (1995), and Walker and Jackson (2008).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have studied the relationships among casinos, other gambling industries, and tax revenues. These papers include Anderson (2005), Anders, Siegel, and Yacoub (1998), Elliott and Navin (2002), Fink and Rork (2003), Kearney (2005), Mobilia (1992), Popp and Stehwien (2002), Ray (2001), Siegel and Anders (1999, 2001), and Thalheimer and Ali (1995). Others have focused on the negative consequences of casino gambling and pathological gambling behaviors like crime and bankruptcy.…”
Section: Brief Literature Reviewmentioning
confidence: 99%